Correlation between the Qualification of Non-formal Education Program with the Graduates Competence - Komar, Oong (Universitas Negeri Semarang, 2017)
Competency become an absolute need for the challenge in the future will be increasingly so severe mainly due to the increasing intensity of competition that services/products that are increasingly complex and risky must be to provided. Competition is no longer local, but regional, and even, international. So, quality must be improved to face work competition. This study is aimed to examine the relationship between the qualifications of non-formal education program with the competence of the graduate as a human resources and the formulation of relation between academic performance and competence/ job performance and the difficulties faced by the graduate users in describing the profession of the graduates of non-formal education. This study is conducted by using a survey research approach to the object of research by using data collection techniques consist of interviews using a questionnaire. From the result of the research, we can see that there is a relationship between the qualification of non-formal education program and the competence of the graduate as human resources and recommendations for the quality development of non-formal education program in the coming years.